INFLUENŢA FACTORILOR SOCIO-DEMOGRAFICI ASUPRA CALITĂŢII VIEŢII POPULAŢIEI ADULTE DIN IAŞI, ROMANIA - Alice Murariu; Doriana Agop Forna; Carman Savin; Norina Consuela Forna (Romanian Dental Association for Education, 2016)
This study investigated the association between socio-demographic factors (gender, age and educational level) and oral health-related quality of life of the adult population in Iasi, Romania. Material and methods: A cross-sectional survey was conducted in 2015 and was selected a sample of 150 subjects with the age between 25-64 years old. Quality of life was assessed with a questionnaire with 15 questions divided into 3 sections: quality of personal life, risk factors for oral health and quality of social life. Results: Related to gender distribution, the self perception of personal and emotional life was reduced for male than female. Educational level has an important influence on attitude to risk factors, like alcohol consumption and a diet low in fruits and vegetables. Significant variations in oral health practices were found according to dental hygiene between high and primary education. The risk for poor quality of life in terms of age distribution was higher for older population than young population. Conclusions: The results of the study confirm the hypothesis that vulnerable people (primary education, low economic status and old population) have a low quality of life in relation with oral health.